(untitled) (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
This case study examines KIA Corporation’s strategic transformation from a budget-focused automaker to a premium brand successfully positioned to serve the expanding luxury automotive market and wealthy consumers. Through comprehensive analysis of market data, financial performance metrics, and strategic initiatives spanning 2015-2024, this research investigates how KIA leveraged the creation of its Genesis luxury division, strategic investments in design and technology, and targeted marketing to capture market share in the rapidly growing premium automotive segment. The study reveals that the global luxury car market is projected to grow from 700.59 billion in 2024 to 1,366.62 billion by 2034, driven primarily by increasing populations of high-net-worth individuals globally. KIA’s transformation strategy, centered on establishing Genesis as a standalone luxury brand, resulted in over one million cumulative vehicle sales within eight years and 8.28% year-over-year growth in 2024. Key success factors identified include sustained quality improvements, distinctive design leadership under Peter Schreyer, early adoption of electric vehicle technology, and strategic separation of luxury operations from the core KIA brand. The findings demonstrate that automotive companies can successfully migrate from value to premium positioning through comprehensive brand transformation, strategic market timing, and sustained investment in quality and innovation. This case provides practical insights for automotive executives and marketing strategists seeking to understand luxury market dynamics and successful brand repositioning strategies in competitive markets.